Anatomical and Cytological Features of Spathoglottis plicata from Java Island - Tatik Chikmawati (Journal of Tropical Life Science, 2013)
Spathoglottis plicata is a ground orchid that displays large variation in flower features. In spite of large variation on morphological characters, its anatomical and cytological characters are not well known. This paper described the leaf anatomical and chromosomal features of S. plicata. Leaf anatomy was observed from both transverse and paradermal sections of leaves. Chromosome numbers were observed from root tip cells. Epidermis of all S. plicata variants comprised of two cell shapes, the rectangle cells located above veins, while the polygonal one located in between veins. Stomatal type was brachitetracyclic, which were only found on lower epidermis. Leaf transversal section comprised of one layer of upper and lower epidermis, spongy mesophyll, and vascular tissue. The number of leaf hair varied depended on the original habitat and altitute. All variants of S. plicata had same chromosome number (2n=40).